Audio Visual Media to Enhance Student Learning Outcomes in Aqidah Akhlak - Yus, Sulhan; Zubaidah, Zubaidah; Suraiya, Suraiya; Mardhiah, Ainal; Nurbayani, Nurbayani; Nisak M. Isa, Qudwatin (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Audio-visual media constitutes a pivotal instructional tool that facilitates the achievement of learning objectives through enhanced student engagement and comprehension. This study aims to examine the comparative effectiveness of storytelling methods and audio-visual media in improving student learning outcomes in the subject of Aqidah Akhlak. Employing a classroom action research approach, data were collected through documentation, observation, and the administration of pre-tests and post-tests. The findings reveal that the storytelling method led to a 20% improvement in student performance, whereas the implementation of audio-visual media resulted in a 90% increase in learning outcomes. These results underscore the superior efficacy of audio-visual media in reinforcing conceptual understanding and fostering meaningful learning experiences among students.